(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The researcher talked about the urban expansion witnessed by the town of Sabaina during the period 1950 to 2011, and the researcher continued to study this expansion by dividing it into four stages of time, indicating the characteristics and characteristics of each stage, referring to the phenomenon of random housing in the town and the reasons for its growth, Talk about the forms and models of residential construction in the town. The researcher relied on the historical method and descriptive and analytical descriptive method by describing this phenomenon. The researcher reached a number of results, the most important of which was: The town of Sabina has undergone a rapid urban transformation from an agricultural village in Al Ghouta to an urban town of the size of the city since the seventies and eighties of the last century as a result of migration and population growth. , And Amran organized 18.6%, and the legislation dealing with the situation of housing random and issued since the sixties of the last century played a negative role in the spread of violations of the construction of gaps in the legislation, and the absence of alternatives.